Strategi Pemasaran dalam Pencapaian Target Produk Simpanan Pada BRI Syari’ah - Kusrini, Eni (TAWAZUN: Journal of Sharia Economic Law, 2019)
The achievement of the savings product target obtained is based on the optimism of BRI Syari'ah employees that the majority of Demak people are Muslims who certainly want a trustworthy service in accordance with their beliefs. In addition, BRI Syari'ah's market share in Demak is increasingly providing opportunities to help customers' needs. This study aims to find out: (1) strategies to achieve the target of marketing savings products at Bank Rakyat Indonesia (BRI) Syari'ah in Demak; (2) and analyze the implementation of efforts to implement strategic analysis on savings products at Bank Rakyat Indonesia (BRI) Syari'ah in Demak. This research is expected to provide various benefits. Theoretically, it is useful in the development of Islamic economics related to shari'ah banking, especially the strategy analysis and achievement of its savings targets. Practically beneficial for practitioners, especially for deposit product managers, as a consideration for managing savings products in shari'ah banking in order to achieve the expected targets.